Sanksi Perpajakan dan Kesadaran Wajib Pajak pada Kepatuhan Wajib Pajak Usaha Mikro, Kecil, dan Menengah (UMKM) di Kabupaten Sorong - Deftiara Felda Pramita N; Pahmi Pahmi; Munzir Munzir (Financial and Accounting Indonesian Research, 2024)
This study aims to determine the effect of tax sanctions, tax administration system and taxpayer awareness on taxpayer compliance. This type of research is quantitative research using primary data and measured by a likert scale. Tha number of samples used in this study were 99 respondents of Micro, Small and Medium Enterprises (MSMEs) taken from the Integrated Business Service Center (IBSC) of Sorong Regency which was determined by purposive sampling. technique. The analysis method used is multiple regression analysis which is processed using Statistical Package for the Sosial Sciences (SPSS) version 25. The data research instrument in this study uses validity and reliability test. this research hypothesis test uses the R2 test, f test, and t test. The result of this study indicate that the tax sanctions variable has a positive and insignificant effect on taxpayer compliance, taxpayer awareness has a positive and significant effect on taxpayer compliance.